Development of Immunoassay Based on Monoclonal Antibody Reacted with the Neonicotinoid Insecticides Clothianidin and Dinotefuran - Seiji Iwasa; Mikiko Uchigashima; Shigekazu Ito; Eiki Watanabe; Shiro Miyake (Sensors, 2012)
Enzyme-linked immunosorbent assay (ELISA) based on a monoclonal antibody (MoAb) was developed for the neonicotinoid insecticide clothianidin. A new clothianidin hapten (3-[5-(3-methyl-2-nitroguanidinomethyl)-1,3-thiazol-2-ylthio] propionic acid) was synthesized and conjugated to keyhole limpet hemocyanin, and was used for monoclonal antibody preparation. The resulting MoAb CTN-16A3-13 was characterized by a direct competitive ELISA (dc-ELISA). The 50% of inhibition concentration value with clothianidin was 4.4 ng/mL, and the working range was 1.5–15 ng/mL. The antibody showed high cross-reactivity (64%) to dinotefuran among the structurally related neonicotinoid insecticides. The recovery examinations of clothianidin for cucumber, tomato and apple showed highly agreement with the spiked concentrations; the recovery rate was between 104% and 124% and the coefficient of variation value was between 1.8% and 15%. Although the recovery rate of the dc-ELISA was slightly higher than that of HPLC analysis, the difference was small enough to accept the dc-ELISA as a useful method for residue analysis of clothianidin in garden crops.